A Positive Emotional-Based Meditation but Not Mindfulness-Based Meditation Improves Emotion Regulation - Valim, Camila P. R. A. T.; Marques, Lucas M.; Boggio, Paulo S. (Frontiers in Psychology, 2019)
Among the various strategies for modulating the components of the emotional responses, the cognitive reappraisal and distraction are highlighted in current researches. As indicated in recent studies, the capacity for emotional regulation can be improved by mindfulness meditation practicing. This practice usually offers benefits to people's cognitive functioning and aims to improve a characteristic that is intrinsic to every human being: the ability to turn attention to the present moment. Importantly, positive emotions might also be effective on emotional regulation and several meditation practices make use of it. Thus, we aimed to compare two meditation modalities: one focused on attention only (mindfulness) and another focused-on attention toward positive emotions (Twin Hearts Meditation - THM). Ninety healthy subjects without any previous experience in meditation were enrolled in this experiment. Of these participants, 30 were submitted to the mindfulness practice with full attention on the observation of thoughts; 30 to the Twin Hearts Meditation (THM); and 30 to a control group (no meditation practice). After one session of meditation, all the participants completed emotional regulation task judging the valence and arousal of pictures with emotional content. In addition to the behavioral data, the participants' psychophysiological measures were recorded via electrocardiography (ECG). The results demonstrate a greater efficacy of THM in suppressing the negative valence of the negative pictures and amplifying the valence of the positive ones. No effect of meditation was observed for the ECG. Our findings indicate that contemplative meditation (THM) can positively influence the emotion regulation ability, even when performed by non-meditators and only once. However, in Mindfulness meditation this same immediate effect was not found. Our findings reveal that faster effects of meditation practices can be obtained by practices that considers either the attentional processing and the positive emotions.